Mutant Allele Frequency-Based Intra-Tumoral Genetic Heterogeneity Related to the Tumor Shrinkage Mode After Neoadjuvant Chemotherapy in Breast Cancer Patients - Zheng, Chun-hui; Liu, Zhao-yun; Yuan, Chen-xi; Dong, Xiao-yun; Li, Hai-mei; Wang, Jin-jin; Zhang, Zhao-peng; Liu, Hong-Ying; Ding, Xiao-yan; Wu, Wendy; Wang, Rui-ru; Wang, Yong-sheng (Frontiers in Medicine, 2021)
The shrinkage mode after neo-adjuvant chemotherapy (NAC) regarding the tumor extent is important to assess the odd of breast-conserving surgery. However, there is no sufficient measurement that predict the shrinkage mode after NAC. In this study, we analyzed pre- and post- treatment formalin-fixed, paraffin-embedded (FFPE) samples from 24 patients to measure the mutations profile using the targeted next-generation sequencing approach with 456 cancer-related genes panel. Meanwhile, Pathological shrinkage mode was reconstructed in three dimensions after surgery and the genetic heterogeneity level was estimated by mutant-allele tumor heterogeneity (MATH). We measured the genetic intra-tumor heterogeneity (ITH) and explored its correlation with the shrinkage mode after NAC. A total of 17 matched pair samples of primary tumor tissue and residual tumor tissue were successful accessed. The most common mutated gene was TP53 and PIK3CA, in both pre- and post- NAC samples. In addition, no recurrent mutations significantly associated with the shrinkage mode. Moreover, MATH value of FFPE samples before and after NAC treatment were analyzed by area under the curve (AUC) of the receiver operating characteristic (ROC), and it is feasible to stratify patients into concentric shrinkage mode (CSM) and non-concentric shrinkage mode (NCSM) in NAC based on the MATH threshold =58. Our findings indicate that MATH value was associated with the shrinkage mode of breast cancer in a nonlinear model. Patients with the MATH value below the cut-off line (58) before and after NAC displayed a concentric shrinkage mode. Area under the ROX curve (AUC) was 0.89, with the sensitivity and specificity were 0.69 and 1, respectively. Our study might provide a promising application of intratumor genetic heterogeneity as measured by MATH to inform surgical choices.